Membangun Kinerja Pegawai yang Optimal melalui Penguatan Motivasi Kerja dan Pengelolaan Beban Kerja pada Dinas Sosial dan PMD Kabupaten Wonosobo - Grafit Pratama; Rinawati Zailani (CV. ALIM'SPUBLISHING, 2026)
This study aims to examine the influence of work motivation and workload on employee performance at the Social Affairs and Community and Village Empowerment Agency (Dinsos PMD) of Wonosobo Regency. The study employs a qualitative approach, utilizing data collection techniques such as in-depth interviews, direct observation, and document analysis. The findings indicate that work motivation—particularly intrinsic motivation, such as a sense of responsibility and the desire to contribute to the community—positively impacts employee performance. Conversely, a lack of extrinsic motivation, such as recognition and incentive systems, acts as a barrier that diminishes work morale. Meanwhile, high and uneven workloads lead to physical fatigue and work-related stress, ultimately affecting employee productivity and performance quality. Nevertheless, highly motivated employees are still able to maintain their performance despite facing heavy workloads. The study concludes that optimal employee performance can be achieved by strengthening work motivation and balancing workloads. Therefore, organizational management capable of balancing appropriate motivation with proportional workload distribution is essential to achieving optimal employee performance.